Presenting symptoms and long‐term survival in head and neck cancer. (15th January 2018) - Douglas, C.M.; Ingarfield, K.; McMahon, A.D.; Savage, S.A.; Conway, D.I.; MacKenzie, K.
Abstract : Objectives: To assess how type and number of symptoms are related to survival in patients with head and neck cancer. Design: Patients were followed up for over 10 years from the Scottish Audit of Head and Neck Cancer (national cohort of head and neck cancer patients in Scotland 1999‐2001). September 2013, cohort was linked to national mortality data. First, second and third presenting symptoms were recorded at diagnosis. Setting: National prospective audit—Scotland. Participants: A subset of 1589 patients, from the original cohort of 1895, who had cancer arising from one of the four main subsites; larynx, oropharynx, oral cavity and hypopharynx. Main outcome measures: Median survival in relation to patients' presenting symptoms. Results: A total of 1146 (72%) males and 443 (28%) females, mean age at diagnosis 64 years (13‐95). There was a significant difference in survival in relation to the number of the patient's presenting symptoms; one symptom had a median survival of 5.3 years compared with 1.1 years for three symptoms. Patients who presented with weight loss had a median survival of 0.8 years, compared to 4.2 years if they did not ( P < .001). Patients who presented with hoarseness had a median survival of 5.9 years compared to 2.6 years without ( P < .001). There was no significant difference in long‐term survival for patients who presented with an ulcer, compared to those that did not ( P = .105). Conclusions: This study highlights the importance of patients' presenting symptoms, giving valuable information in highlighting appropriate "red flag" symptoms and subsequent treatment planning and prognosis.